Choice of methods can determine which behavioral determinates are identified for targeting in future behavior change interventions: Increasing antibiotic adherence in Pakistan. (March 2022) - Taj, Umar; Schmidtke, Kelly Ann; Vlaev, Ivo; Read, Daniel
When developing a behavioral intervention, formative research should be conducted to determine which behavioral barriers and facilitators to target. This is often done using qualitative interviews, but quantitative surveys may also be used. The current study examines the consequences of applying descriptive (rank order and t -tests) versus predictive (regression) quantitative analyses on intervention development, specifically for increasing antibiotic course completion. For demonstrative purposes, 1892 adults in Pakistan completed a cross-sectional survey that measures a comprehensive set of barriers/facilitators to their course completion. The descriptive and predictive analyses disagreed regarding which barriers/facilitators to prioritize. Reasons to prefer predictive analyses are discussed.